The Gatekeepers: How the White House Chiefs of Staff Define Every Presidency - Chris Whipple (Crown, 2017)
What do Dick Cheney and Rahm Emanuel have in common? Aside from polarizing personalities, both served as chief of staff to the president of the United States—as did Donald Rumsfeld, Leon Panetta, and a relative handful of others. The chiefs of staff, often referred to as "the gatekeepers," wield tremendous power in Washington and beyond; they decide who is allowed to see the president, negotiate with Congress to push POTUS's agenda, and—most crucially—enjoy unparalleled access to the leader of the free world. Each chief can make or break an administration, and each president reveals himself by the chief he picks.